Factors Affecting Resin Yield in Chir - Deshmukh, D. K.; Payal, P. S. (Indian Forester, 1964)
The article deals with both climatic and edaphic factors affecting resin yield during various months of a tapping season. Amongst these factors evapotranspiration seems to be the most important factor. Response to these factors seems to vary with plantations raised from different seed origins. The article also attempts to give a formula for estimation of resin yield.